The Role of the Village Government in Community Empowerment for Economic Development in Maholo Village, East Lore District, Poso Regency - Fitriyani, F.; Yunus, Santi; Anam, Haerul; Nasruddin, Anwar; Tallesang, Mukhtar (Manunggal Halim Jaya, 2024)
This study aims to determine the role of the Maholo Village government in empowering the farming community for village economic development. The research method used in this study is a qualitative method. Based on the results of the research, it was found that the role of the Maholo Village government in empowering the farming community is still lacking. This is due to the lack of communication between the community and the village government, the lack of socialization carried out by the government about the empowerment of the farmer community, the uneven provision of assistance for the farming community in Maholo Village, the empowerment carried out for community groups, especially the farmer group, is uneven, so that there are some people who are less enthusiastic about the community empowerment program around 30-40%.